2012
DOI: 10.11002/kjfp.2012.19.2.243
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Nutritional Components of Fermented Black Jujube

Abstract: The physicochemical properties and nutritional components of fermented black jujube (FBJ) were compared with those of dried jujube (DJ) to improve their utilization as food materials. The moisture contents and brix of the DJ and FBJ were 22.6% and 6.07 brix, and 10.36% and 7.23 brix, respectively. Their L values were 34.78 and 31.82, and the a and b values of DJ were higher than those of FBJ. DJ had a lower water activity level (0.75) than FBJ (0.45), but FBJ had a higher amount of reducing sugar and soluble p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Specifically, 289.97 mg/100 g was obtained from the fermentation process while only approximately 198.04 mg/100 g were obtained from the EE, and the amounts in the FE were much higher than previously reported amounts, such as 28.5 mg/100 g . The increase in acacetin content is considered attributable to the fact that as organic acids such as lactic acid increased through lactic acid bacteria fermentation, the resulting pH reduction affected A. rugosa xylem cell walls, etc., such that more acacetin could be eluted . In addition, a previous study conducted by Itokawa et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, 289.97 mg/100 g was obtained from the fermentation process while only approximately 198.04 mg/100 g were obtained from the EE, and the amounts in the FE were much higher than previously reported amounts, such as 28.5 mg/100 g . The increase in acacetin content is considered attributable to the fact that as organic acids such as lactic acid increased through lactic acid bacteria fermentation, the resulting pH reduction affected A. rugosa xylem cell walls, etc., such that more acacetin could be eluted . In addition, a previous study conducted by Itokawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, acacetin has been reported to have antioxidant effects, but A. rugosa has not yet been reported to have tyrosinase and melanogenesis inhibition. The main result of this study is supported by other reported data: Saponin contents increased in lactic acid bacteria fermented extracts of the ginseng berry, and a study on fermented black jujube identified that physicochemical characteristics and nutritional contents increased after fermentation . However, the increases in antioxidant effects resulting from increases in acacetin enhanced the inhibition of tyrosinase activities and reinforced melanogenesis suppression, thereby improving tyrosinase and melanogenesis inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…증숙을 통해 제조된 발효 흑대추는 기능성 성분의 추출율이 매우 높고 생대추에 비해 항산화 활성이 증가되었 다 (10). 또한 증숙된 발효더덕은 생더덕에 비해 유용성분의 함량이 높았으며, 증숙가공 공정을 통해 항산화 활성이 증 진되었다 (11,12 …”
unclassified